Formulation And Evaluation Of Metoclopramide Hydrochloride Microbeads By Ionotropic Gelation Method - Hemalatha, K (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT Metoclopramide hydrochloride is an antiemetic and prokinetic agent used in the treatment of gastroparesis and gastroesophageal reflux disease1, 6. The half life of metoclopramide hydrochloride is 4-6 hours. Metoclopramide hydrochloride microbeads were prepared by ionotropic gelation method using sodium alginate in combination with guargum and HPMC as drug release modifiers in various proportions to overcome the drug related adverse effects. No significant drug-polymer interactions were observed in FT-IR studies. The drug entrapment efficiency increased progressively with increasing concentration of both sodium alginate and coating polymer resulting in the formation of larger microbeads entrapping greater amounts of the drug2. The drug entrapment efficiencies were obtained in the range of 50.02Â±1.41% to 78.21Â±1.03%. The size and surface characteristics were determined by an optical microscope and SEM. No significant swellings of microbeads are seen in Hcl with pH 1.2. Invitro drug release profile of metoclopramide hydrochloride from microbeads was examined in simulated gastric fluid pH 1.2 and simulated intestinal fluid pH 7.4.Microbeads coated with guargum and HPMC shows optimum level of sustained release. The drug release was found to follow non-fickian diffusion obeying zero order kinetics.